Use Application Quiz in Model Tgt Learning (Team Games Tournament) to Improve Elementary School Multiplication Counting Skills - Hartini, Sri; Nurasiah, Iis; Nurmeta, Irna Khaleda (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to describe the use of the quizizz application in the TGT (Team Games Tournament) learning model to improve elementary school multiplication numeracy skills in class III of SDN Sindangsari, Sukabumi Regency with a total of 28 students. The research method used was classroom action research (PTK) Kemmis and Mc Taggart model research design which was carried out in two cycles. Each cycle consists of planning, implementation, action and observation, and reflection. Data collection techniques use tests in theform of pretests and posttests, and non-tests in the form of observations, interviews, field notes and documentation. The data analysis technique used is descriptive qualitative. From the pre-cycle learning completion cycle, only 29% or 8 students completed because they still used a formal learning model consisting of lectures, exercises and questions and answers. After implementing the Quizizz application in the TGT learning model in cycle I, it has been proven that there has been an improvement, although it is not yet visible significantly, completion was only 64% or 18 students who completed. Then, from the evaluation results of the previous cycle, the research continued with cycle II by adding improvements, the completion of learning results in increasing multiplication ability increased by 89% or 25 students. Therefore, the research was stopped classically because it had reached or exceeded the 85% achievement indicator. By combining the TGT Model with the use of the Quizzizz application in mathematics learning, teachers can create a learning environment that is stimulative, collaborative and interesting for students. This can help improve students' math skills through a team-based learning approach and utilizing digital technology as an effective learning tool.